Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.7764/psykhe.24.1.641
|View full text |Cite
|
Sign up to set email alerts
|

Creative Soups for the Soul: Stories of Community Recovery in Talca, Chile, After the 2010 Earthquake

Abstract: This study, conducted in Talca, Chile, a year and a half after a massive natural disaster, focused on creative thinking and art production as manifestations of resilience. Purposive sampling was used to recruit participants through community leaders and programs. Ten survivors whose houses were damaged or destroyed during the 2010 earthquake were willing to participate in semi-structured interviews that included verbal narratives and an art response. Systematic analysis illuminated conscious and latent psychol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…While Mohr was careful not to assert a cause-effect relationship between the arts and post-traumatic healing, she found that her respondents drew on the arts to attribute meaning to their traumatic experiences. Further research is needed to understand the mechanisms by which arts interventions can shape recovery processes and support post-disaster wellbeing in different socio-cultural contexts (Bender et al, 2015).…”
Section: The (Neglected) Role Of the Arts In Recovery Processesmentioning
confidence: 99%
See 2 more Smart Citations
“…While Mohr was careful not to assert a cause-effect relationship between the arts and post-traumatic healing, she found that her respondents drew on the arts to attribute meaning to their traumatic experiences. Further research is needed to understand the mechanisms by which arts interventions can shape recovery processes and support post-disaster wellbeing in different socio-cultural contexts (Bender et al, 2015).…”
Section: The (Neglected) Role Of the Arts In Recovery Processesmentioning
confidence: 99%
“…While Mohr was careful not to assert a cause-effect relationship between the arts and post-traumatic healing, she found that her respondents drew on the arts to attribute meaning to their traumatic experiences. Further research is needed to understand the mechanisms by which arts interventions can shape recovery processes and support post-disaster wellbeing in different socio-cultural contexts (Bender et al, 2015). In comparing arts interventions and recovery outcomes in Talca, Chile (after the 2010 earthquake) and New Orleans (after the 2005 Hurricane Katrina), Bender et al (2015, p. 11) found ‘essential differences’ in community solutions and the ways in which the content of artworks ‘linked to cultural and contextual narratives’.…”
Section: The (Neglected) Role Of the Arts In Recovery Processesmentioning
confidence: 99%
See 1 more Smart Citation